The media marketing mix and its role in confronting political crisis strategies: An analytical study of a sample of Iraqi university professors - الطائي, يوسف حجيم سلطان; رشيد, ساكار عزيز; كشكول, حسين محمد علي (Sulaimani Journal for Humanities, 2019)
This research study aims to understand the impact of media marketing mix on political crisis and how media marketing mix can be used to manage political crisis in an efficient and effective manner. The study was based on the descriptive approach, through an analytical study of the views of a sample of Iraqi university professors, especially those working in the faculties of political science, media and management. The importance of this study is to apply media marketing mix with its seven dimensions to political crises in order to reduce people’s anger. The study sample consisted of (125) individuals. The statistical analysis was carried out according to the statistical package program for the study variables, namely, marketing mix of the media with its seven dimensions and political crisis strategies with its six dimensions. The study has concluded that if media marketing mix is professionally used, it could reduce the risks of political crisis. The study recommends using media marketing mix strategy to influence public opinion and reduce the negative effects of the politics.
Keywords: Media marketing mix; political crisis strategies